IDENTIFICATION OF THE PREREQUISITES FOR RELIGIOUS RADICALIZATION AS THE BASIS FOR THE FORMATION OF PSYCHOLOGICAL IMMUNITY - Касимова З. Х. (American Journals Publishing, 2026)
This article examines the need for timely identification of the causes and roots of religious radicalization. The author presents a number of prerequisites and factors of incorrect perception of religious information by modern youth.
Keywords: Religious radicalization, prerequisites, content analysis, perception, youth, mass media, radicalization.